A method to construct high-precision complex pore digital rock. (31st October 2018) - Dong, Huaimin; Sun, Jianmeng; Golsanami, Naser; Cui, Likai; Jiang, Liming; Yan, Guoliang; Yan, Weichao; Li, Yafen
Abstract: X-ray CT scanning is one of the main methods to study the pore structure of the rocks. However, low resolution is currently one of the major challenges of this method, which does not allow for the identification of microscopic pores. Even though adopting images of higher resolutions could reflect the microscopic pores of the rocks, due to the small size of the scanned rock sample in the x-ray CT scanning method, the rock parameters cannot be effectively obtained, especially for the rocks with strong heterogeneity. This would cause the loss of important pore information, such as fractures' information. Focusing on this problem, the current research tries to propose a method for constructing high-precision digital rocks of complexly porous rocks. This method is based on the simultaneous application of x-ray CT scanning images, nuclear magnetic resonance measurements, as well as mercury injection experimental data and fractal discrete fracture network. These methods effectively compensate for the shortcomings of the scanning method where it cannot capture pores smaller than the scanning resolution and for the lack of fracture information due to rock sampling. The research results showed that compared with the digital rock models constructed by single-resolution scanning, the high-precision complex pore digital rock constructed by this method can effectively improve the accuracy of the results of porosity and permeability calculations. These results were closer to the results of rock physics experiments. This approach provides a solid foundation for the numerical simulation of rock parameters in unconventional reservoirs with complex pore structures, such as carbonate, tight sandstone and shale reservoirs.